Planejamento experimental aplicado aos estudos de degradação forçada do fármaco Ticagrelor - Cunha, Danilo Rodrigues (2020)
Stability indicating tests are an essential part during pharmaceutical drug production, besides being a mandatory step for the regulation and approval from the regulatory agencies. Forced degradation consist of an exposure of the drug substance to rough stress conditions in order to verify the intrinsic stability of the drug molecule and identify its degradation products. These tests are usually conducted by univariate analysis being the pharmaceutical drug submitted to different stress conditions, such as: acid, alkaline and oxidative media, photolysis and humidity exposure. This work aims to evaluate by multivariate analysis the forced degradation of Ticagrelor using design of experiments. Two designs were built, the first one evaluated 3 variables at 5 levels: pH (2; 4; 6; 8; 10), concentration of hydrogen peroxide in % v / v (0; 0.25; 0.5; 0, 75; 1) and temperature in °C (26; 33; 40; 47; 54). On the second one, the UV radiation was evaluated qualitatively while pH and Temperature were evaluated in a 2-variables design in the same levels as the first one. For each experiment, the degradation percentage of Ticagrelor was calculated and the results were used to build mathematical models using multiple regression. In the experiments without UV radiation, the concentration of H2O2 followed by pH were the most significant variables in the degradation process of Ticagrelor. In the experiments with UV irradiation, only the variable pH was significant. There are indications that an interaction between the variables pH and UV radiation is possible in this design. The temperature and other interactions between the variables were not significant in both experiments. All experiments were subjected to chromatographic separation by HPLC-UV and the assays with a good chromatographic profile were subjected to analysis by HPLC-IT-MS to structural elucidation of the degradation products. Thus, experimental planning proved to be a useful tool in conducting forced degradation studies, allowing the evaluation of the effect of multiple variables, as well as their interactions in the degradation process of Ticagrelor.